Comparison Of The Effectiveness Of Moringa And Spinach Leaf Capsules In Increasing Hemoglobin Levels Among Anemic Pregnant Women In The Third - Agustini, Ni Ketut Farida; Sunarsih, Sunarsih; Rachmawati, Fijri; Astriana, Astriana (JKM (Jurnal Kebidanan Malahayati), 2024)
Background Data from the Bandar Lampung City Health Office in 2022 shows the proportion of anemia in pregnant women is 37.25%, namely pregnant women with Hemoglobin levels < 8 gr%/dl is 2.41%, Hb is 8-11gr%/dl is 36.3%. Anemia occurs in pregnant women due to insufficient production of red blood cells by the consumption of nutrients, especially iron. Iron can be obtained by consuming Moringa leaves. Another vegetable that is believed to contain a lot of iron is spinach, especially green spinach. The Purpose of the study was to find out the comparison of the effectiveness of moringa and spinach leaf capsules in increasing Hb levels in third trimester pregnant women with anemia in the Working Area of the Panjang Community Health Center, Bandar Lampung City, in 2023.Methods This study uses a type of quantitative research, with a quasi-experimental design. The population in this study were all pregnant women with their third trimester of gestation who made ANC visits at the Panjang Community Health Center in Bandar Lampung City and experienced anemia with a total of 47 people. A sample of 36 respondents. The data collection technique uses a questionnaire sheet and the data analysis used is the independent t-test.The results showed that the average hemoglobin level in third trimester pregnant women before consuming moringa leaf capsules was 10.46 gr/dl, and in the spinach leaf group was 10.37 gr/dl. The average hemoglobin level in third trimester pregnant women after consuming moringa leaf capsules was 11.87 gr/dl, and in the spinach leaf group was 11.24 gr/dl. Conclusion There is a difference in the effectiveness of moringa and spinach leaf capsules in increasing Hb levels in TM III pregnant women with anemia in the Working Area of the Panjang Community Health Center, Bandar Lampung City, 2023 (p value 0.000). Suggestion It is hoped that health workers can optimize counseling regarding the consumption of moringa leaf capsules to increase hemoglobin levels in third trimester pregnant women with anemia. Keywords: Moringa leaf capsules, spinach leaves, Hb levels